How is China's coke price related with the world oil price? The role of extreme movements - Guo, Y.; Wen, X.; Wu, Y.; Guo, Xiumei (Elsevier BV * North-Holland, 2016)
© 2016.This paper focuses on the relationship between the world oil price and China's coke price, particularly with respect to extreme movements in the world oil price. Based on a daily sample from 2009 to 2015 and the ARJI-GARCH models and copulas, our empirical results show that China's coke price and the world oil price are characterized by GARCH volatility and jump behaviors. Specifically, negative oil price shocks lead to falls in China's coke returns on the following day while positive oil prices have no significant effects. In addition, current coke returns positively respond to the very recent oil price jump intensity, and a time-varying and volatile lower tail dependence is found between the world oil price and China's coke price. Our results are expected to have implications for coke producers and users and policy makers.